Developing Hiwaruna as Arabic Conversation Book for Speaking Skills in Islamic Boarding School - Kholisin Kholisin; Beta Fadiatun Nisa’; Faris Khoirul Anam; Moh. Fery Fauzi (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
This study aims to develop an Arabic conversation textbook at the Islamic Boarding School Themes For Students of Al Kamal Islamic Boarding School Blitar, East Java. The development is a solution of unavailability textbook to speak daily Arabic in Islamic boarding schools. This study uses the ADDIE development model. The subjects of the product trial were class 1D students at the Al Kamal Islamic Boarding School. The data collection techniques used were observation, interviews, and questionnaires. The result of this research is a daily Arabic conversation book entitled "Hiwaruna" for learning speaking skills at the Al Kamal Islamic Boarding School Blitar. This book contains themes that are closely related to daily life in Islamic boarding schools. The results of product validation from material and media experts obtained an average value of 82.50% with the information that it is very suitable for use in Arabic speaking learning at Islamic boarding schools.